Penerapan Aplikasi Line Webtoon dan Pengaruhnya terhadap Keterampilan Membaca Siswa Kelas XI SMA YWKA Palembang - Triani, Lisa; Houtman, Houtman (Lentera: Jurnal Ilmiah Kependidikan, 2022)
This study aims to determine whether the Line Webtoon application has an effect on students’ reading skills which were previously not good enough after using the Line Webtoon aplication. The type of research used in this study is a quantitative experimental method. The result of the research that has been done is that there is an effect of the Line Webtoon application on reading skills in class XI students of SMA Yayasan Wanita Kereta Api (YWKA) Palembang, which is significant because it is proven that tcount is greater that ttable at a significant level of 0,05%. After comparing the test result of the control class with the experimental class, it was found that tcount ttabel 3,188 0,1982 at a significant level of 0,05% with dk 68, namely the difference in the average score of 18.76 and the average value of the experimental class was 21.47. thus, the hypothesis which states that “ Line Webtoon application affects the reading skills of class XI students at SMA Yayasan Wanita Kereta Api (YWKA) Palembang” is proven to be true.